2015
DOI: 10.1111/jsm.13037
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Flibanserin in Women with Hypoactive Sexual Desire Disorder: A Systematic Review and Meta-Analysis

Abstract: Introduction Flibanserin, is a postsynaptic agonist of serotonin receptor 1A and an antagonist of serotonin receptor 2A, has been shown to increase sexual desire and reduce distress in women with hypoactive sexual desire disorder (HSDD). Aim We carried out a systematic review and meta-analysis to assess the efficacy and safety of the drug in women with HSDD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…223 Meta-analyses have shown that flibanserin resulted in approximately 1 additional satisfying sexual event every 2 months in premenopausal women. 224,225 This drug has not been studied in patients with cancer or survivors, but it is a reasonable option to discuss with premenopausal survivors with low or lack of desire, libido, or intimacy; other options for these survivors include bupropion and buspirone. 226 These drugs have been studied in a few trials involving noncancer populations.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…223 Meta-analyses have shown that flibanserin resulted in approximately 1 additional satisfying sexual event every 2 months in premenopausal women. 224,225 This drug has not been studied in patients with cancer or survivors, but it is a reasonable option to discuss with premenopausal survivors with low or lack of desire, libido, or intimacy; other options for these survivors include bupropion and buspirone. 226 These drugs have been studied in a few trials involving noncancer populations.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…In these trials, FLI 100 mg once daily significantly increased sexual desire and function while decreasing distress relative to placebo (PBO). These findings were further confirmed by a recent meta‐analysis (Gao, Yang, Yu, & Cui, ), and similar findings were reported in a phase III trial in naturally postmenopausal women with HSDD (Simon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analyses by Gao, Yang, Yu, and Cui (2015) and Jaspers et al (2016), examining efficacy and risks associated with flibanserin treatment, are excellent examples of variability in the strengths and weaknesses of meta-analysis, specifically -the file-drawer effect‖ to which Balon and Seagraves were referring. Gao et al (2015) restricted their sample to four published RCTs and reported a standardized mean difference in SSEs of .59.…”
Section: Are Meta-analyses the Answer?mentioning
confidence: 99%
“…Gao et al (2015) restricted their sample to four published RCTs and reported a standardized mean difference in SSEs of .59. Jaspers et al (2016) replicated this effect using the same sample of published studies with an additional published study in which only women who showed improvement in an open-label phase were retained and randomized to treatment or placebo (Goldfischer et al, 2011 (2016) and Clayton and Pyke (2016) suggested that future research could focus on direct comparisons between pharmaceutical and psychological treatments, or combination treatments for low desire in women.…”
Section: Are Meta-analyses the Answer?mentioning
confidence: 99%